Aquatic Toxicology Notes: Predicting the Fate and Effects of Aquatic and Ditchbank Herbicides: SL236/SS455, 4/2006 - Wilson, Chris (EDIS, 2006)
The purpose of this document is to introduce readers to: 1) factors affecting the exposure of aquatic organisms to aquatic herbicides, and 2) useful methods for estimating potential risks of acute mortality for non-target aquatic organisms. This document is SL236, a fact sheet of the Soil and Water Science Department, UF/IFAS Extension. Original publication date April 2006.